2009
DOI: 10.1016/j.aquatox.2009.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of binary mixtures of estrogen and antiestrogens on Japanese medaka (Oryzias latipes)

Abstract: a b s t r a c tIt is supposed that the estrogenic effects of estrogenic chemicals will be balanced by the presence of other endocrine-disrupting chemicals (EDCs) with different properties. However, little convincing research into this issue has been carried out to date. In the present study, the combined effects of EDCs with estrogenic and antiestrogenic activities were assessed using a 21-day reproduction assay with the Japanese medaka (Oryzias latipes) as an in vivo model. Natural estrogen (17␤-estradiol, E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Experimental results obtained by exposure to several individual EDCs demonstrate that co-exposure to EDCs with different MOAs can have distinct, divergent outcomes [22], [53]. Estrogenic effects, for example, can be neutralized or reinforced by antiestrogenic exposure, as it was shown in this and several other studies [22], [53].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Experimental results obtained by exposure to several individual EDCs demonstrate that co-exposure to EDCs with different MOAs can have distinct, divergent outcomes [22], [53]. Estrogenic effects, for example, can be neutralized or reinforced by antiestrogenic exposure, as it was shown in this and several other studies [22], [53].…”
Section: Discussionsupporting
confidence: 68%
“…Estrogenic effects, for example, can be neutralized or reinforced by antiestrogenic exposure, as it was shown in this and several other studies [22], [53]. Antiestrogenic exposure itself, however, might not exhibit any effects.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In a similar study conducted in zebrafish, no significant effect on the HSI in males or females was found, but the GSI value was significantly higher in males exposed to 0.3 mg/L tribromophenol than in females [29]. Sun et al [30] reported that HSI was significantly increased in male Japanese medaka exposed to 17-b-estradiol (E 2 ) (200 ng/L) [30]. The lack of sensitivity of the HSI and GSI found in the present study suggests that these endpoints might not provide useful information for short-term exposure of adult fish to estrogenic activity.…”
Section: Discussionmentioning
confidence: 84%
“…This assumption was tested in a study by assessing 17β-estradiol (E2) and the anti-estrogens letrozole (an aromatase inhibitor) and tamoxifen, individually and in combination, using a 21-day reproduction in vivo assay with the Japanese medaka (Oryzias latipes) (Sun et al, 2009). This assumption was tested in a study by assessing 17β-estradiol (E2) and the anti-estrogens letrozole (an aromatase inhibitor) and tamoxifen, individually and in combination, using a 21-day reproduction in vivo assay with the Japanese medaka (Oryzias latipes) (Sun et al, 2009).…”
Section: Mixture Effects Of Estrogens and Anti-estrogensmentioning
confidence: 99%